Evaluation of abatacept administered subcutaneously in adults with active rheumatoid arthritis: impact of withdrawal and reintroduction on immunogenicity, efficacy and safety (phase Iiib ALLOW study). Issue 1 (13th September 2011) - Kaine, Jeffrey; Gladstein, Geoffrey; Strusberg, Ingrid; Robles, Manuel; Louw, Ingrid; Gujrathi, Sheila; Pappu, Ramesh; Delaet, Ingrid; Pans, Miranda; Ludivico, Charles
Abstract : Objectives: To assess the effect of a temporary interruption in subcutaneous (SC) abatacept on immunogenicity, safety and efficacy in patients with active rheumatoid arthritis despite methotrexate in a phase III trial. Methods: Following a 12-week open-label introduction (period I; intravenous abatacept loading dose and weekly fixed-dose SC abatacept 125 mg), patients were randomised 2:1 to double-blind SC placebo or SC abatacept for 12 weeks (period II). At the end of period II, patients receiving SC abatacept continued treatment and patients on placebo were reintroduced to SC abatacept (12-week open-label period III). The co-primary end points were ELISA-detected immunogenicity rate and safety at the end of period II. Efficacy was also monitored. Results: Of 167 patients entering period I, 72% qualified for period II; during periods II and III, three patients discontinued treatment. Mean (SD) disease duration was 6.6 (6.5) years and Disease Activity Score 28 was 4.8 (0.8). The primary end point was met, with a non-significant increase in immunogenicity upon withdrawal (7/73 placebo vs 0/38 abatacept in period II; p=0.119) which was reversed upon reintroduction of SC abatacept (2/73 vs 1/38, end period III). Safety was comparable regardless of withdrawal, with no unexpected events upon reintroduction. Two patients experienced reactions at the SC injection site. On withdrawal, patients experienced slight worsening in efficacy which improved following reintroduction. Conclusions: Overall immunogenicity to SC abatacept is low, consistent with intravenous abatacept, and is not significantly affected by a 3-month interruption and reintroduction. This stop–start schedule was well tolerated, with little impact on safety and efficacy. These are important considerations for the clinical use of SC abatacept. ClinicalTrials gov: Identifier NCT00533897